The Effect of EWOM, Subjective Norms, Perceived Behavioral Control and Product Quality On The Intention To Buy Subsidized Housing - Nurhidayat, Ridwan; Suroso, Arif Imam; Prabantarikso, Mahelan (Indonesian Journal of Business and Entrepreneurship, 2023)
Kuningan city view (KCV) is one of the housing estates that sell subsidized houses. In 2021, sales did not reach the target. This study analyzes various factors that influence the purchase intention of subsidized housing in KCV housing through eWOM variables, subjective norms, perceptions of behavior control, and product quality, understanding the characteristics of respondents and formulating managerial implications to increase the purchase intention of subsidized housing in KCV housing. This research involved 100 prospective buyer respondents who met the criteria of being able to buy subsidized houses that were domiciled in the Kuningan district and its surroundings, using a voluntary sampling technique. Data was collected through questionnaires which were distributed directly to respondents and online. The analysis in this study uses Partial Least Square Structural Equation Modeling (PLS-SEM). The majority of respondents were in the age group of 26-29 years and the average number of respondents who were interested in buying subsidized housing was already married, around 79%. There are 62 respondents who work in the private sector, while civil servants, military, and police are around 22 respondents and the rest are self-employed around 16 respondents.The results indicate that eWOM, subjective norm, and product quality have a significant effect on purchase intention, while perceptions of behavioral control have no significant effect. Based on the research, the housing developer need to maximize the potential of eWOM in conducting marketing and providing information related to information, it is necessary to improve product quality such as public facilities, increase marketing collaboration with all stakeholders in the subsidized housing program which aims to all parties can benefit. Keywords: eWOM, purchase intention, subsidized housing, SEM-PLS, subjective norm